Time perspective in extreme situation - O G Kvasova (Peoples' Friendship University of Russia (RUDN University), 2010)
The article gives the new definition of the concept of time perspective in the view of postnonclassic paradigms in psychology. It shows the temporal unity of the past, present and future in life story of personality in the context of conception of temporal work.